Enhancing the Pupils’ Discovery Approach in Teaching Water Cycle to the Grade 3 Pupils: A Lesson Study Based Approach - Pagara, Charity Rose Absin; Rapadas, Fritzie C; C. Nara, Edzel Marie; B. Puentenegra, Marlae Natalie; M. Galarpe, Arbe Joe; A. Paclar, Fetish Kayle; U. Onting, Mary Gretel; Ubanan, Luzminda C; Naive, Pauline M; Peralta, Rubylinda E (Journal of Learning Improvement and Lesson Study, 2022)
This collaborative study was designed to enhance the discovery skills of Grade 3 pupils. There were 38 participants and data were collected from recorded virtual brainstorming sessions, observation notes, and Online Classroom Actual Implementation of Lesson design conducted in two cycles. It has 2 cycles with the second cycle having an improved version of the lesson plan. Results showed that there were more pupils who generated answers based on the discovery approach in the 2nd cycle of lesson implementation using the refined version of the lesson plan. Furthermore, results of the formative test during the second cycle indicates the benefit of lesson study in enhancing the discovery skills of the pupils leading to mastery of the lesson concept. The teachers’ inquiry-based instruction was a factor considered to improve the pupils’ discovery skills. Hence, through lesson study, the factors were identified to help improve the pupils’ discovery skills.